TINJAUAN YURIDIS ATAS PEMBATALAN PERKAWINAN SERTA AKIBAT HUKUMNYA (STUDI PUTUSAN No. 1009/Pdt. G/2009/PA. Mdn. Pada Pengadilan Agama Kelas I-A Medan) - NURUL MARIATI SIMANJUNTAK (PREMISE LAW JURNAL, 2016)
In the Islamic point of view, marriage is the foundation of life in social interaction and the noblest deed in managing. If in its implementation, a marriage does not fulfill its legitimate requirements, it can be cancelled. The cancellation can be caused by the violation against marriage procedures and material. Therefore, a marriage cancellation was filed to the Court in the jurisdiction where the husband and wife live (Article 25 of Marriage Law No. 1/1974) in the judge’s verdict on the request of the husband or wife, and/ or of the other parties. Keywords: Cancellation, Marriage, Legal Consequence